5-gen-leadership : leading 5 generations in schools in the 2020s - White, Mark Edward; Sheninger, Eric C. (Thousand Oaks : Corwin, 2022)
School leaders will find: Practical tips for transitioning to 5-Gen Leadership Advice for recruiting and retaining Millennial and Gen Z teachers Advice for creating a welcoming environment for Gen Alpha Resources to help everyone succeed despite challenges such as COVID-19 Vignettes from representative teachers and leaders from each generation.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Educational leadership; School management and organization